Stat3 and Stat4: members of the family of signal transducers and activators of transcription. - Zhong, Z (1994)
The deduced amino acid sequence of two members of the signal transducers and activators of transcription (STAT) family from the mouse are described. Comparison with the deduced protein sequence of the two previously described genes (Stat91 and Stat113), discovered because of their activation as transcription factors after interferon-induced tyrosine phosphorylation, shows several highly conserved regions, including the putative SH3 and SH2 domains. The conserved amino acid stretches likely point to conserved domains that enable these proteins to carry out the several required functions they are known and proposed to carry out. While Stat1 and Stat3 are widely expressed, Stat4 expression is restricted to testis, thymus, and spleen. Antiserum to Stat3 detects a major approximately 92-kDa protein and a minor approximately 89-kDa protein, while antiserum to Stat4 precipitates one major protein of approximately 89 kDa.